Diagnostic performance of contrast-enhanced ultrasonography for predicting therapeutic response to radiofrequency ablation in patients with hepatocellular carcinoma: a meta-analysis - Ji Dong; Xin Hu; Lin Li; Fei-Yan Jing; Jin-Jin Chen; Jun Chen (Discover Oncology)
Abstract Purpose Contrast-enhanced ultrasound (CEUS) is frequently used to detect residual or recurrent liver cancer following radiofrequency ablation (RFA) therapy for hepatocellular carcinoma (HCC). However, disagreements persist regarding its diagnostic efficacy. This study aimed to assess the diagnostic value of contrast-enhanced ultrasonography (CEUS) for detecting residual or recurrent hepatocellular carcinoma (HCC) after radiofrequency ablation (RFA) using a meta-analytic approach. Methods PubMed, Embase, and the Cochrane Library were searched for studies published up to March 2024. The diagnostic value of CEUS was assessed using sensitivity, specificity, PLR, NLR, diagnostic odds ratio (DOR), and area under the receiver operating characteristic (ROC) curve (AUC). Results This meta-analysis included 13 studies with 802 HCC patients (964 lesions). CEUS demonstrated high sensitivity (0.88, 95% CI: 0.80–0.93) and specificity (0.98, 95% CI: 0.96–0.99) for detecting residual or recurrent tumors after RFA. The positive likelihood ratio (PLR) was 46.88 (95% CI: 20.69–106.24) and the negative likelihood ratio (NLR) was 0.12 (95% CI: 0.07–0.21). The diagnostic odds ratio (DOR) was 222.77 (95% CI: 100.23–495.16), with an AUC of 0.96 (95% CI: 0.94–0.97). Factors such as publication year, study design, ethnicity, blinding, patient age, contrast agent usage, and reference tests were found to influence CEUS’s diagnostic accuracy. Conclusion CEUS exhibited excellent diagnostic performance for detecting residual or recurrent tumors in HCC patients after RFA. Therefore, it should be employed in clinical practice for evaluating therapeutic response to RFA. Registration Number INPLASY202440089.